Transcriptomic and enzymatic analysis of peroxidase families at the early growth stage of halophyte ice plant (Mesembryanthemum crystallinum L.) under salt stress - Li-Ching Hsieh; Chia-Che Lee; Kai-Fu Zhang; Hui-Hsien Chang; Cheng-Hsun Li; Hsuan-Jung Huang; Hungchen Emilie Yen (Botanical Studies)
Abstract Ice plant (Mesembryanthemum crystallinum L.) is a halophyte and an inducible CAM plant. Ice plant seedlings display moderate salt tolerance, with root growth unaffected by 200 mM NaCl treatments, though hypocotyl elongation is hindered in salt-stressed etiolated seedlings. Superoxide anion accumulation was prominent in cotyledons and primary leaves but decreased in root tissues over time, with no significant effect from salt treatment. Hydrogen peroxide levels initially surged in both control and salt-treated seedlings, with higher and more persistent accumulation in the salt-treated seedlings. The activities of H2O2-scavenging ascorbate-glutathione cycle enzymes ascorbate peroxidase (APX), monodehydroascorbate reductase, and dehydroascorbate reductase increased, while guaiacol-dependent peroxidase activity decreased and catalase activity showed no change, indicating APX activity as the primary response to salt stress. Salt-induced APX activities were detected mainly in the microsomal fraction for light-grown seedlings and the cytosolic fraction for etiolated seedlings, highlighting plastids as the primary site of ROS accumulation under salt stress. An RNA-seq analysis of etiolated seedlings revealed about 8% unigenes showing more than a four-fold change in expression after a 6-h 200 mM NaCl treatment. GO enrichment analysis indicated that differentially expressed genes (DEGs) with increased transcript abundance were associated with ion transport, antioxidant activity, and stress responses, while DEGs with decreased transcript abundance were linked to metabolic and biosynthesis processes such as ribosomal protein synthesis and cell wall formation. This indicates that salt stress hinders growth but enhances ion homeostasis and stress response mechanisms. The expression of all eight APX genes were induced by a 48-hour salt treatment, with varying expression patterns. For class III peroxidase family, 14 out of 53 identified unigenes qualified as DEGs. The time-course expression patterns revealed that the transcript levels of McPrx4.1, McPrx12.1, and McPrx12.3 increased, while McPrx60.3 decreased. These findings highlight the distinct roles of class III peroxidases in balancing plant growth and stress responses, advancing our understanding of the mechanisms behind salt tolerance in halophytes. This study comprehensively analyzed changes in gene expression, antioxidant enzyme activity, and ROS accumulation in ice plant seedlings. Unveiling these responses will advance our understanding of the growth–stress balance in the intrinsic salt tolerance in halophytes.